(untitled) (SAARC Journal of Agriculture, 2022)
Pesticide application against insect pest infestation is environmentally unsafe and costly. An attempt was taken to evaluate the solar light trap as ecofriendly and cost-effective approach in Transplanted Aman rice (BRRI dhan32) field at Barhatta Upazila (Sub-district) in Netrokona district of Bangladesh. It was found that rice pest like Rice yellow stem borer, Rice leaf roller, Green leaf hopper, Brown plant hopper, Rice leaf miner, Rice gall midge, White leafhopper, Rice bug, Rice ear cutting caterpillar, White-backed planthopper, Rice caseworm, Grasshopper, Rice skipper and Rice beetle were the major insects that captured under the solar light traps. Some beneficial insects were also attracted by the trap these were Ladybird beetle, Water scavenger, Giant water bug, Ground beetle, Rove beetle, Damsel fly. All the harmful and the beneficial insects were belonging the order of Lepidoptera, Hemiptera, Orthoptera, Coleoptera, Diptera and Odonata. Though the mean yield of rice was statistically insignificant in both fields, the light trap installed fields required the less frequency of pesticides than the control fields which ultimately rendered the low pesticides cost in a great extent. On an average 1,034 BDT was reduced in per hectare. SAARC J. Agric., 20(1): 171-183 (2022)